Kepastian Hukum Ikrar dan Akta Wakaf Bawah Tangan untuk Legalisasi Wakaf melalui Program Lintas Sektor di Kantor Pertanahan Kabupaten Sukabumi - Yogi Septio Adi Nugroho; Ani Yumarni; Sudiman Sihotang (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the legal certainty of informal waqf pledges and deeds, as well as the effectiveness of the Cross-Sector Program (LINTOR) in the legalization of waqf land in Sukabumi Regency. The research employs an empirical juridical method with statutory and sociological approaches, using document analysis, field observations, and interviews with the Office of Religious Affairs (KUA), the Land Office, and related stakeholders. The findings indicate that underhand waqf practices do not comply with Law Number 41 of 2004 on Waqf, thereby weakening legal evidentiary power and obstructing the waqf land certification process. Although the LINTOR Program conceptually facilitates the acceleration of waqf land registration, its implementation remains constrained by administrative deficiencies, weak inter-institutional coordination, and low public legal awareness. This study emphasizes the need to strengthen the role of KUA as Waqf Pledge Deed Officials, reinforce cross-sector technical regulations, and enhance legal literacy to ensure legal certainty in waqf land management.